2016
DOI: 10.1007/978-1-4939-6475-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Mammary Gland Development: Elucidation of In Vivo Morphogenesis Using Murine Models

Abstract: During the past 25 years, the combination of increasingly sophisticated gene targeting technology with transplantation techniques has allowed researchers to address a wide array of questions about postnatal mammary gland development. These in turn have significantly contributed to our knowledge of other branched epithelial structures. This review chapter highlights a selection of the mouse models exhibiting a pubertal mammary gland phenotype with a focus on how they have contributed to our overall understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 177 publications
0
20
0
Order By: Relevance
“…The mammary gland is an excellent system to study stem cells, microenvironments, and development as the vast majority of cellular growth and differentiation occurs during puberty [7]. The glandular epithelium undergoes vast proliferation and differentiation during puberty.…”
Section: Introductionmentioning
confidence: 99%
“…The mammary gland is an excellent system to study stem cells, microenvironments, and development as the vast majority of cellular growth and differentiation occurs during puberty [7]. The glandular epithelium undergoes vast proliferation and differentiation during puberty.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that mammary development at puberty is triggered by the main steroid hormones estradiol and progesterone (for review see 2 ). Indeed, experiments with PR -deficient mice demonstrated that, at puberty, progesterone is not essential for ductal elongation but is critical in inducing side-branching 24 .…”
Section: Discussionmentioning
confidence: 99%
“…At the end of its development, the mammary epithelium has the appearance of an elaborate tree of ducts and alveoli. After parturition, the alveolar epithelium starts to be fully functional, with mammary epithelial cells secreting milk proteins into the lumen of the alveoli for lactation 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive and metabolic hormones, such as estrogen, progesterone (P 4 ), placental lactogen, prolactin (PRL), OT, growth hormone (GH), glucocorticoids, thyroid hormone and insulin, well coordinate and dominate mammary gland development including ductal branching, alveolar bud development and secretion during pregnancy or lactation (Neville et al, 2002;Macias and Hinck, 2012;McNally and Stein, 2017). Estrogen and GH primarily regulate ductal morphogenesis by binding to their receptors during puberty and pregnancy in mice (Kleinberg et al, 2000;McBryan and Howlin, 2017). A balance between P 4 and PRL controls alveolar morphogenesis during pregnancy in mice (Neville et al, 2002;Leehy et al, 2018), while PRL, GH, glucocorticoids, thyroid hormone, and insulin govern milk secretion in mice or rats (Vonderhaar and Ziska, 1989;Flint and Gardner, 1994;Menzies et al, 2010).…”
Section: Introductionmentioning
confidence: 99%